Optimizing intrauterine insemination: A systematic review and meta‐analysis of the effectiveness and safety of clinical treatment add‐ons - Elpiniki Chronopoulou; Andrea Gaetano‐Gil; Sadaf Shaikh; Claudia Raperport; Bassel H. Al Wattar; Gabriel Ruiz‐Calvo; Javier Zamora; Priya Bhide (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Intrauterine insemination (IUI) is one of the most widespread fertility treatments. However, IUI protocols vary significantly amongst fertility clinics. Various add‐on interventions have been proposed to boost success rates. These are mostly chosen arbitrarily or empirically. The aim of this systematic review and meta‐analysis is to assess the effectiveness and safety of add‐on interventions to the standard IUI protocol and to provide evidence‐based recommendations on techniques used to optimize the clinical outcomes of IUI treatment. Material and Methods Systematic review and meta‐analyses were performed in accordance with PRISMA guidelines. A computerized literature search was performed from database inception to May 2023. Randomized controlled trials (RCTs) were included reporting on couples/single women undergoing IUI with any protocol for any indication using partner's or donor sperm. A meta‐analysis based on random effects was performed for each outcome and add‐on. Three authors independently assessed the trials for quality and risk of bias and overall certainty of evidence. Uncertainties were resolved through consensus. Primary outcomes were ongoing pregnancy rate (OPR) or live birth rate (LBR) per cycle/per woman randomized. Registration number PROSPERO: CRD42022300857. Results Sixty‐six RCTs were included in the analysis (16 305 participants across 20 countries). Vaginal progesterone as luteal phase support in stimulated cycles was found to significantly increase LBR/OPR (RR 1.37, 95% CI 1.09–1.72, I2 = 4.9%) (moderate/low certainty of the evidence). Endometrial scratch prior/during stimulated IUI cycles may increase LBR/OPR (RR 1.44, 95% CI 1.03–2.01, I2 = 1.8%), but evidence is very uncertain. Results from two studies suggest that follicular phase ovarian stimulation increases LBR/OPR (RR 1.39, 95% CI 1.00–1.94, I2 = 0%) (low certainty of evidence). No significant difference was seen for the primary outcome for the other studied interventions. Conclusions The findings of this systematic review and meta‐analysis suggest that vaginal luteal phase progesterone support probably improves LBR/OPR in stimulated IUI treatments. In view of moderate/low certainty of the evidence more research is needed for solid conclusions. Further research is also recommended for the use of endometrial scratch and ovarian stimulation. Future studies should report on results according to subfertility background as it is possible that different add‐ons could benefit specific patient groups.